Integrating the Educational Principles of Maria Montessori in the Process of Pedagogical Support for Pupils with Learning Disabilities - Ratner, Faina Lazarevna; Efimova, Victoria Leonidovna (International Review of Management and Marketing, 2016)
The purpose of the present article was to search for new ways of individual pedagogical support for primary school children with learning disabilities. The article describes the mechanisms for putting the educational principles of Maria Montessori into the system of pedagogical support for children with learning disabilities, which apply the exercises of practical life to a real social environment. The objective of the exercises was to develop universal learning activities, e.g., the ability to plan and manage a child’s activity, to reflect its results, to build up communication, to encourage cognitive development. Keywords: learning disabilities, individual pedagogical support, Maria Montessori, universal learning activities JEL Classifications: I20; I23